Orientalist Studies on Methodology of Repetition in the Holy Quran A Critical Study - Syed Mahmudul Hasan; Md. Fakar Uddin (USIM Press, 2024)
Vol. 16 No. 2 (2020): Journal of Maʿālim al-Qurʾān wa al-Sunnah